Citizens' Perceptions of Domestic Violence News on Social Media Platforms: A Critical Discourse Analysis - Taufik Rakhmadi; Ani Rakhmawati; Arjay Julio (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Netizens increasingly encounter and interpret news about domestic violence against women on social media, shaping public discourse and potentially influencing responses in law, policy, and everyday life. Objective: To determine netizens’ perceptions of news about domestic violence against women on social media platforms through a critical discourse analysis. Method: This study employed a critical approach. Data sources comprised primary data (interviews) and secondary data (documentation). Data were processed and analyzed using descriptive qualitative methods within a critical discourse analysis framework. Result: Findings indicate that domestic violence against women is perceived as a violation not only of legal principles and human rights but also of social norms. Across the analyzed discourse, domestic violence is consistently framed as a human rights violation that must be eliminated. Conclusion: Social media discourse reflects a strong normative stance against domestic violence, reinforcing its status as a human rights violation and highlighting the need for collective action and zero tolerance toward perpetrators. Contribution: This study contributes to scholarship in Indonesia by clarifying public perceptions of domestic violence on social media and offering applied insights for gender sociology, family sociology, and criminology. The results can inform prevention, intervention, and awareness strategies across academic, policy, and community contexts.